Model Pembelajaran Team Games Tournament Untuk Meningkatkan Keaktifan Siswa Pada Mata Pelajaran Qur’an Hadits Kelas VIII DI MTS Muhammadiyah Alamanda Kec. Kinali Kab. Pasaman Barat - Indah Nurbaiti; Bambang Trisno; Endang Sukawati (Indonesian Research Journal on Education, 2023)
Active learning is a way of learning that can encourage students or educators in the learning process, where active learning can support the achievement of learning objectives. Based on this research, based on several problems that researchers found in class VIII MTs Muhammadiyah Alamanda Kec. Kinali Kab. Pasaman Barat. Especially in the subject matter of Al-Qur’an Hadits which concerns the subject matter of verses or hadits. Where in learning there are still some students who are not active in learning and these students feel bored or bored and often go in and out of class, so the learning process does not run optimally in class. These various problems arise from the learning model used by educators who are not appropriate, resulting in a luck of interest in learning for students if there are tasks of memorizing verses and hadits in the Qur’an Hadits Subject. Therefore, a very effective model is needded, namely by using the Team Games Tournamen (TGT) learning model as a support for increasing the activity of students in the learning process in the Al-Qur’an Hadits subject at MTs Muhammadiyah Alamanda Kec. Kinali Kab. Pasaman Barat. The type of research used in this study is qualitative research which aims to solve problems based on data presentation and data analysis. The objects in this study were students of class VIII MTs Muhammadiyah Alamanda Kec. Kinali Kab. Pasaman Barat Academic Year 2022/2023. Which has a number of students of approximately 82 students. Whith class VIII A female 21 students, VIII B Female 21 students, VIII C male 20 students, and VIII D male 20 students. The research data was obtained by direct observation, and interviews with teacher of the Qur’an Hadits subject. The results of this study indicate that the activenesess of students in the Qur’an Hadits subject which concerns the understanding of verses and also hadits uses the Team Games Tournament (TGT) learning model in class VIII MTs Muhammadiyah Alamanda. Meanwhile, after applying the Team Games Tournament (TGT) learning model, it can be presented with player point, namely players with Top Scorers have a presentage of 80 %, players with High Middle Scorer have a precentage of 10 %, players with Low Middle Scorer have a percentage of 7 %. And players with Low Scorer have a percentage of 3 %. With these results, it can be said that the Team Games Tournament (TGT) learning model can support the activeness to understand the subject matter and makes it easier for students to memorize verses or hadits in the Qur’an Hadits subject. With this, educators can apply the Team Games Tournament (TGT) learning model whwn students have bored while studying, are bored, lazy and often go in and out of class. Or educators can use the Teams Games Tournamnet (TGT) model according to the material taught to students.